Sports medicine and the accident and emergency medicine specialist. Issue 3 (1st May 2002) - Abernethy, L; McNally, O; MacAuley, D; O'Neill, S
Abstract : Background: Sport and exercise related injuries are responsible for about 5% of the workload in the accident and emergency (A&E) department, yet training in sports medicine is not a compulsory part of the curriculum for Higher Specialist Training. Aim: To determine how A&E medicine consultants and specialist trainees view their role and skill requirements in relation to sports medicine. Method: A modified Delphi study, consisting of two rounds of a postal questionnaire. Participants were invited to rate the importance of statements relating to the role and training of the A&E specialist in relation to sports injuries (six statements) and the need for knowledge and understanding of defined skills of importance in sports medicine (16 statements). Value of research: This provides a consensus of opinion on issues in sport and exercise medicine that have educational implications for A&E specialists, and should be considered in the curriculum for Higher Specialist Training. There is also the potential for improving the health care provision of A&E departments, to the exercising and sporting population.